Application of Online Mode Professional Development in Enhancing Pedagogical and Professional Competencies in Early Grade Primary School Teacher - Syahruddin; Ahdan; Ernawati (Lembaga Pengembangan Pendidikan dan Pembelajaran, Universitas Negeri Malang in Collaboration with Asosiasi Pendidik dan Pengembang Pendidikan Indonesia (APPI), 2019)
The purpose of this study is to explain the online mode of professional development application in improving teacher competency of learners. The competencies intended in this study are pedagogic competence and professional competence. The research design was carried out in quantitative and qualitative forms. The number of research samples is 30 people. Data collection method used is online media validiation and performance tests. Data analysis used descriptive statistics. The results showed validation in the online mode of continuing professional development of the learning teacher had an average value of total validity = 3.5. Thus, this value is included in the category